The association between the receipt of lipid lowering therapy and HIV status among veterans who met NCEP/ATP III criteria for the receipt of lipid lowering medication. - Freiberg, Matthew S; Leaf, David A; Goulet, Joseph L; Goetz, Matthew B; Oursler, Krisann K; Gibert, Cynthia L; Rodriguez-Barradas, Maria C; Butt, Adeel A; Justice, Amy C (Journal of general internal medicine, 2009)
To examine the association between HIV infection status and the receipt of lipid lowering therapy based on National Cholesterol Education Program/Adult Treatment Panel (NCEP/ATP III) guidelines and to assess whether HIV viral load and hepatitis C (HCV) status alters that association.
Keywords: Adult; Aged; Coronary Disease; Cross-Sectional Studies; Hepatitis C, Chronic; HIV Infections; Humans; Hypercholesterolemia; Hypolipidemic Agents; Male; Middle Aged; Odds Ratio; Physician's Practice Patterns; Prospective Studies; Veterans; Viral Load